Cenários para investigação matemática no ensino fundamental: uma experiência com ensino híbrido na modalidade rotação por estações - Guimarães, Débora Sudatti (2019)
This dissertation presents the results of a research conducted from the perspective of Hybrid Teaching, in the mode Rotation by Seasons, in Scenarios for Research. It has as research problem to investigate what are the implications of the practice of Station Rotation in Research Scenarios in the construction of active and reflective knowledge of equations of the second grade with students of the 9th grade of elementary school. The methodology was constituted in a qualitative approach, through a pedagogical intervention research, in which the analysis reflected on the practice and the practice. For the production of research data were considered the activities produced by the students, the teacher/researcher's logbook and a questionnaire applied to the students at the end of the intervention. The data were submitted to Discursive Textual Analysis. The results of the analysis allowed us to conclude that the Hybrid Teaching, in the mode Rotation by Stations in Scenarios for Research configures an alternative with high potential for the construction of the active and reflective knowledge of the students, besides demonstrating, also, the way the relations of interdependent autonomy, task proactivity, critical thinking, creativity in situations, and articulation with reality. The research also revealed that the Rotation by Seasons in Scenarios for Research allows a range of possibilities for educational innovation, besides contributing to improve the pedagogical practice of the teacher/researcher, which highlights the planning of the classes as the fundamental basis for their role is efficient in the educational process.